2013
DOI: 10.1093/ije/dyt148
|View full text |Cite
|
Sign up to set email alerts
|

Profile: Manhica Health Research Centre (Manhica HDSS)

Abstract: The Manhiça Health Research Centre, established in 1996 in a rural area of southern Mozambique, currently follows around 92 000 individuals living in approximately 20 000 enumerated and geo-positioned households. Its main strength is the possibility of linking demographic data and clinical data to promote and conduct biomedical research in priority health areas. Socio-demographic data are updated twice a year and clinical data are collected on a daily basis. The data collected in Manhiça HDSS comprises househo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(144 citation statements)
references
References 13 publications
2
140
0
Order By: Relevance
“…The ODK software provides most of the functions that we required, but certain things, like being able to edit a form once it has been finalised, are currently not possible. Other research sites, including HDSSs, have developed their own software for such purposes [1,21,22], which was beyond our current capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The ODK software provides most of the functions that we required, but certain things, like being able to edit a form once it has been finalised, are currently not possible. Other research sites, including HDSSs, have developed their own software for such purposes [1,21,22], which was beyond our current capacity.…”
Section: Discussionmentioning
confidence: 99%
“…22 A detailed description of MDH, CISM, and the study area can be found elsewhere. 23 CISM provides personnel as well as valuable resources and laboratory diagnosis to MDH.…”
Section: Methodsmentioning
confidence: 99%
“…Since 1996, the Centro de Investigação em Saú de de Manhic¸a has conducted continuous demographic surveillance covering a population of approximately 95 000 inhabitants in an area of 500 km 2 [17]. Passive morbidity surveillance was established in parallel at the MDH and peripheral health posts in the area, whereby all pediatric hospital admissions and outpatient attendances are registered onto standardized questionnaires following standard procedures.…”
Section: Study Area and Populationmentioning
confidence: 99%